Stepping to the Beat: Feasibility and Potential Efficacy of a Home-Based Auditory-Cued Step Training Program in Chronic Stroke - Wright, Rachel L.; Brownless, Simone Briony; Pratt, David; Sackley, Catherine M.; Wing, Alan M. (Frontiers in Neurology, 2017)
Background: Hemiparesis after stroke typically results in a reduced walking speed, an asymmetrical gait pattern and a reduced ability to make gait adjustments. The purpose of this pilot study was to investigate the feasibility and preliminary efficacy of home-based training involving auditory cueing of stepping in place. Methods: Twelve community-dwelling participants with chronic hemiparesis completed two 3-week blocks of home-based stepping to music overlaid with an auditory metronome. Tempo of the metronome was increased 5% each week. One 3-week block used a regular metronome, whereas the other 3-week block had phase shift perturbations randomly inserted to cue stepping adjustments. Results: All participants reported they enjoyed training, with 75% completing all training blocks. No adverse events were reported. Walking speed, TUG time and DGI scores (median [inter-quartile range]) significantly improved between baseline (speed = 0.61 [0.32,0.85 ]m.s-1; TUG = 20.0[16.0,39.9]s; DGI = 14.5[11.3,15.8]) and post stepping training (speed = 0.76 [0.39,1.03]m.s-1; TUG = 16.3 [13.3,35.1]s; DGI = 16.0[14.0,19.0]) and was maintained at follow-up (speed = 0.75 [0.41, 1.03]m.s-1; TUG = 16.5 [12.9,34.1]s; DGI = 16.5[13.5,19.8]). Conclusion: This pilot study suggests that auditory-cued stepping conducted at home was feasible and well-tolerated by participants post-stroke, with improvements in walking and functional mobility. No differences were detected between regular and phase-shift training with the metronome at each assessment point.